Focal nodular hyperplasia of the liver: an unusual association with diabetes mellitus in a child and review of literature - Trizzino Antonino; Tropia Serena; Cardella Francesca; Alaggio Rita; Farruggia Piero; Ferrara Francesca; D'Angelo Paolo (BMC, 2010)
Abstract Hepatic hemangioma, adenoma and focal nodular hyperplasia are the most frequent benign lesions of the liver, but they are all infrequent among pediatric population. The reports of focal nodular hyperplasia in children have recently increased in number, with many cases associated to drug intake, particularly to chemotherapy. We here describe, to our knowledge, the first case of focal nodular hyperplasia in association with diabetes mellitus in childhood.